2019
DOI: 10.1111/bor.12388
|View full text |Cite
|
Sign up to set email alerts
|

Glacier outburst floods reconstructed from lake sediments and their implications for Holocene variations of the plateau glacier Folgefonna in western Norway

Abstract: A sudden release of large volumes of water during a glacier outburst flood (GLOF) is a major hazard worldwide. Here, we identify the sedimentary signature of glacial and non‐glacial processes, including GLOFs, based on lacustrine sediments from the distal glacier‐fed Lake Buarvatnet in western Norway. Historically documented GLOFs in 2002 CE and during the 1980s CE are identified in the 210Pb‐ and 14C‐dated sediments. These events have the same sedimentary signature as 12 earlier events throughout the Holocene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 76 publications
(127 reference statements)
0
21
0
Order By: Relevance
“…Boes et al, 2018;Røthe et al, 2019;Piret et al, 2021). In such settings, GLOF deposits were also represented as deposits that are finer than the background sediments (Røthe et al, 2019).…”
Section: Glacial Lake Outburst Flood Signature In Fjord Sedimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Boes et al, 2018;Røthe et al, 2019;Piret et al, 2021). In such settings, GLOF deposits were also represented as deposits that are finer than the background sediments (Røthe et al, 2019).…”
Section: Glacial Lake Outburst Flood Signature In Fjord Sedimentsmentioning
confidence: 99%
“…Although previous studies have investigated GLOF deposits in lake settings (e.g. Xu et al, 2015;Røthe et al, 2019), little is known about how GLOFs are recorded in fjord sediments. The only GLOF deposits that have been described in marine sediments are those of Disenchantment Bay (Alaska) (Willems et al, 2011), which are composed of stratified mud, sand and diamicton, formed by sediment gravity flows and hypopycnal plume sedimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…they preferentially trap larger particles (i.e. the bedload), leaving only the finer suspended fraction of the sediment for downstream export (Gjerde et al, 2016; Røthe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sediments deposited in lakes have high preservation potential, and previous studies have shown how valuable lake sediment studies are to reconstruct the frequency of past natural hazards in Scandinavia, such as floods (Bøe et al, 2006; Nesje et al, 2001; Støren et al, 2010, 2016), glacier outburst floods (Røthe et al, 2019; Xu et al, 2015) and mass-wasting events (Nesje et al, 2007; Nielsen et al, 2016; Sletten et al, 2003; Vasskog et al, 2011). Recent developments in technical and analytical capacity allow us to use high-resolution x-ray computed tomography (CT) to visualise the lacustrine sediment sequence and quantify the volume of material found in the lake.…”
Section: Introductionmentioning
confidence: 99%